THE USE OF THE LATEST COMPUTER TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN THE DIAGNOSIS AND TREATMENT OF ENDOCRINE DISEASES IN CHILDREN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
One of the most important tasks facing medical science in the 21st century is a deeper study of the human body, early detection of diseases and effective treatment. For this purpose, computer technologies and artificial intelligence systems are being widely introduced worldwide. This approach is gaining increasing importance, especially in the field of endocrine diseases in children. Because the endocrine system is a complex mechanism that ensures the growth, development, metabolism and humoral balance of the child, and any disruption in it negatively affects the functioning of the child's entire organism.